2001
DOI: 10.1016/s0014-5793(01)02819-8
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking phosphorylation at Ser‐48 strongly reduces surface expression of human macrophage scavenger receptor class A: implications on cell motility

Abstract: The role of human macrophage scavenger receptor A1 (SRA1) in the development of atherosclerotic lesions is still scarcely defined. Substituting serine 48 in human SRA1 by an aspartate demonstrated that (1) surface expression of the mutated receptor was 13-fold decreased; (2) the amount of cell-associated Texas red-labeled acetylated low density lipoprotein (LDL) in mutant receptor-expressing cells was almost threefold reduced; (3) the migration of mutant receptor-transfected cells towards surfaces coated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…225 Substituting serine 48 in human SR-A1 by an aspartate demonstrated that surface expression of the mutated receptor was 13-fold decreased; the amount of cell-associated Texas red-labeled AcLDL in mutant receptor-expressing cells was almost threefold reduced; and the migration of mutant receptortransfected cells toward surfaces coated with Ox-LDL decreased by almost 60% compared to cells that were transfected with the wild-type receptor. 226 These observations indicate that phosphorylation of the cytoplasmic part of SR-A1 may help to modulate the residence time of macrophages in atherosclerotic lesions and again emphasize the importance of phosphorylation events in receptor upregulation and accumulation of modified lipids (Fig. 5).…”
Section: S I G N a L I N G E V E N T S A S S O C I A T E D W I T H mentioning
confidence: 66%
See 1 more Smart Citation
“…225 Substituting serine 48 in human SR-A1 by an aspartate demonstrated that surface expression of the mutated receptor was 13-fold decreased; the amount of cell-associated Texas red-labeled AcLDL in mutant receptor-expressing cells was almost threefold reduced; and the migration of mutant receptortransfected cells toward surfaces coated with Ox-LDL decreased by almost 60% compared to cells that were transfected with the wild-type receptor. 226 These observations indicate that phosphorylation of the cytoplasmic part of SR-A1 may help to modulate the residence time of macrophages in atherosclerotic lesions and again emphasize the importance of phosphorylation events in receptor upregulation and accumulation of modified lipids (Fig. 5).…”
Section: S I G N a L I N G E V E N T S A S S O C I A T E D W I T H mentioning
confidence: 66%
“…5). 226 Since in JNK2 negative macrophages, SR-A is upregulated, it is possible that JNK2 negatively regulates a kinase, which has a role in phosphorylation-dependent SR-A upregulation. These evidences suggest that JNK mediates SR-A phosphorylation (Fig.…”
Section: S I G N a L I N G E V E N T S A S S O C I A T E D W I T H mentioning
confidence: 99%
“…Furthermore, we also found that the EDXD motif, consisting of Glu 12 , Asp 13 , and Asp 15 , may not be necessary for endocytosis. The phosphorylation of serine residues proximal to the membrane has also been demonstrated to be necessary for SR-A internalization (19,21), indicating the complicated nature of regulation of receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phosphorylation of Ser48 was reported to act as a key mediator for internalization. 23 However, the influence of the heterogeneity in SR-A cytoplasmic domain on mediating uptake of ligand into cell would not be neglected. For example, a significant difference in the structure of cytoplasmic domain exists between human and murine SR-A, The murine SR-A has 5 more amino acid residues in its cytoplasmic domain than does human SR-A, and their homology is 76% (blast in NCBI).…”
Section: Discussionmentioning
confidence: 99%